Intention to Purchase Foreign Halal Food Products among Muslim Consumers Using S-O-R Framework - Mohd Ossman, Nurul Sarah; Ling, Pick-Soon; Mohmed Wasli, Siti Marhamah (International Review of Management and Marketing, 2025)
The Islamic economy has rapidly growth due to the increase in the Muslim population and also their consumption expenditure. Due to the paucity of evidence on the factors that affect Muslim consumers to purchase foreign Halal food products, this study intends to investigate the factors that affect the intention of Muslim consumers to purchase foreign Halal food products. A research framework that underlies the Stimulus-Organism-Response model has been developed, with Halal certification, Halal knowledge, Halal awareness, and perceived reputation as stimuli, and attitudes as internal cognitive organisms, while purchasing intention as a response. Throughout the data collection, a total of 211 valid responses were gathered. The results from the partial least squares-structural equation modelling showed that Halal certification, Halal knowledge, Halal awareness, and perceived reputation positively influenced attitudes. Besides, consumers’ purchase intention is positively significantly affected by attitudes. These findings offer crucial understanding related to the subject matters as it would benefit the stakeholders in promoting foreign Halal food products in Muslim-dominated countries. Furthermore, the findings also further enrich the extant knowledge in Islamic marketing and consumer Halal consumption behaviour as the evidence was verified by utilizing the stimulus-organism-responses framework.